Pengaruh Literasi Ekonomi dan Gaya Hidup Terhadap Perilaku Konsumtif Mahasiswa Perempuan - Soleman Do; Ari Data; Fernando Saragih (Varied Knowledge Journal, 2026)
This study is motivated by the increasing consumptive behavior among female students in the digital era, which is characterized by easy access to online shopping, various promotions, discounts, social media trends, and modern lifestyles that encourage purchasing based on desires rather than needs. Although many previous studies have discussed the influence of economic literacy and lifestyle on consumptive behavior, most of them still examine these two variables separately and do not specifically focus on female students. This study aims to analyze the influence of economic literacy and lifestyle on the consumptive behavior of female students at Universitas Nusa Cendana. This study uses a quantitative approach with an explanatory (causal) research design. The sample consists of 120 female students selected through the simple random sampling technique. Data were collected using a Likert-scale questionnaire and then analyzed using multiple linear regression. The results show that economic literacy and lifestyle have a positive and significant influence on consumptive behavior, both partially and simultaneously. The coefficient of determination value of 88.5% indicates that most consumptive behavior is influenced by these two variables, while the remaining percentage is affected by other factors outside the scope of this study. This study is expected to contribute to strengthening economic education studies related to the consumptive behavior of female students.